Hyperhomocysteinaemia and multiple aneurysms. Issue 784 (February 1991) - Colwell, N.; Clarke, R.; Robinson, K.; Keane, F.; O'Briain, S.; Graham, I.
Abstract : Homozygous homocystinuria, the most common genetic disorder of transulphuration, is associated with elevated plasma concentrations of homocystine, homocysteine, multiple clinical abnormalities and life-threatening thromboembolism. Several instances of vascular aneurysms have also been documented. More recently, an association between premature occlusive vascular disease and the heterozygous state has been proposed. We now report an unusual case in whom multiple aneurysms were associated with heterozygous homocystinuria.